Analysis of good agricultural practices in an integrated maize-based farming system - Lazaro, V.; Rajendran, S.; Afari-Sefa, Victor; Kazuzuru, B. (Informa UK Limited, 2017)
Profitability due to use of good agricultural practices (GAPs) is important for improving farmer return on investment. Although GAPs are theoretically expected to be profitable, actual returns accrued to farmers may not necessarily be realized due to shortfalls in profit to farmers after harvest. Farmers cultivate vegetables because of their high farmgate values and profitability per unit area compared to field crops. However, farmers sometimes experience reduced profits due to lack of awareness and technical know-how on improved technologies, lack of bargaining power at market, and lack of access to market information and high-value markets. The objective of the study was to measure gross margin of GAPs introduced to farmers using a financial cost–benefit analysis approach. In 2013, a field survey of 45 randomly selected farm households was administered to elicit enterprise data on production practices including Tomato (Solanum lycopersicum L.) and other crops before intervention of GAPs. A similar survey was carried out in the GAP intervention area in 2014 from 55 randomly selected farm households. Integrating GAPs within existing maize-based farming systems yielded an average gross margin of US$1870·ha−1 for vegetable producers who primarily produce tomato, African Eggplant (S. aethiopicum L.), cv. DB3, and Amaranth (Amaranthus spinosusL.), cv. Madiira 1, compared to standard farmer practices that yielded a gross margin of US$1846·ha−1 during the study. Profit from the introduced GAPs was not statistically different from traditional practices within the short time duration. Whether the introduced GAPs could enhance farmer net crop income and livelihood over the long term needs to be determined.